Elevated pulse pressure and its associations with demographic and clinical parameters in a clinically representative sample of outpatients with psychotic disorders - Christopher Holmberg; Jarl Torgerson; Andreas Gremyr (BJPsych Open, 2022)
Elevated pulse pressure is associated with metabolic and neurocognitive diseases. Preliminary small-scale studies among patients with psychotic disorders have indicated that these patients had an increased pulse pressure compared with controls. However, it is unclear whether and how these associations are manifested among larger heterogenous samples of patients with psychotic disorders. We examined elevated pulse pressure and its associations with demographic and clinical characteristics in a clinically representative sample of outpatients with psychotic disorders (n = 1289). In a subsample (n = 343), we also examined associations with six domains of functioning. Controlling for age and cardiovascular disease, body mass index (BMI) and employment status independently predicted the odds ratio of having elevated pulse pressure. Elevated pulse pressure was also primarily associated with the physical domains of functioning. Outpatients with psychotic disorders that have high BMI and are unemployed thus seem to be at increased risk for elevated pulse pressure and should therefore be particularly considered for blood pressure screenings.